The psychofortological experiences of master's degree students in professional psychology programmes : an interpretative phenomenological analysis - Nel, Lindi (University of the Free State, 2011)
The aim of this qualitative study was to explore and describe the psychofortigenic experiences of master’s degree students in professional psychology programmes in South Africa. Since most research on the topic of master’s students in psychology is conducted from a pathogenic paradigm, this study aimed to describe these students’ experiences from a positive psychology approach. Eight participants were purposively selected from four universities. The participants engaged in reflective writings and three semi-structured interviews over a one-year span. Four rich cases were identified and data were analyzed according to Interpretative Phenomenological Analysis (IPA). The phenomenological approach of this study was useful in exploring the lived worlds of the participants. Themes were conceptualized and operationalized within the structure of psychological well-being (Ryff, 1989), general positive psychology literature, as well as literature based on the development and dynamics of master’s students in professional psychology training. Thorough interpretation of the findings yielded eight themes of significance across the cases, which were all indicative of enhanced levels of psychological well-being as an outcome of the participants’ experiences. The first theme refers to specific goals and high motivation levels with regard to becoming a psychologist, which created a strong sense of meaning and contributed to personal growth in the students. Self-reflection as a trigger for selfawareness was identified and found to be a powerful element that can contribute to personal growth and autonomy in these students’ journeys. The findings further indicated that personal growth is a positive outcome of the experience. Intrapersonal dynamics also aided participants towards greater self-acceptance. The study showed that participants identified interpersonal growth as a positive outcome of the experience and that positive relationships with others were found to be a useful coping mechanism throughout the year; thus, contributing to the psychological well-being domain of environmental mastery. Supervision practices positively influenced the psychological well-being domain of autonomy and were also proven to contribute towards the participants’ personal growth. Furthermore, spiritual deepening resulted from the experience of being a master’s student in professional psychology and spirituality was employed as an effective coping mechanism. The group dynamics of the master’s class and the relationships with class colleagues were found to be crucial factors that positively contributed to the participants’ psychological well-being, specifically within the domain of autonomy and positive interpersonal relationships. Lastly, the findings indicated that the participants identified and employed individual coping strategies throughout their journey, which contributed to the domain of environmental mastery. Overall, the important finding was that, while the experience of becoming a psychologist is known to be a long and difficult journey, it can also be rewarding and holds the potential to enhance psychological well-being. The study concluded with a discussion of the implications, limitations and strengths of the study as well as recommendations for future research.

Die doel van hierdie kwalitatiewe studie was om die psigofortologiese ervarings van meestersgraadstudente in professionele sielkundeprogramme in Suid-Afrika te verken en te beskryf. Aangesien die meeste van die navorsing oor die onderwerp van meestersgraadstudente in sielkunde vanuit ’n patologiese paradigma gedoen word, poog hierdie studie om die studente se ervarings vanuit ’n positiewe sielkunde benadering te beskryf. Agt deelnemers van vier universiteite is deur middel van ’n doelgerigte steekproef gekies. Die deelnemers het reflektiewe skryfwerk gedoen, asook drie semi-gestruktureerde onderhoude oor ’n tydperk van een jaar ondergaan. Vier ryk gevalle is geïdentifiseer en die data is deur middel van Interpretatiewe Fenomenologiese Analise geanaliseer. Die fenomenologiese benadering in hierdie studie het nuttig geblyk om die leefwêreld van die deelnemers te ondersoek. Temas is gekontekstualiseer en geoperasionaliseer binne die struktuur van psigologiese welstand (Ryff, 1989), literatuur oor positiewe sielkunde, asook literatuur gebaseer op die ontwikkeling en dinamika van meestersgraadstudente in professionele opleiding in sielkunde. Deeglike interpretasie van die bevindinge het agt beduidende temas tussen die gevalle gelewer, wat almal op hoër vlakke van psigologiese welsyn as ’n uitkoms van die deelnemers se ervarings gedui het. Die eerste tema verwys na die spesifieke doelwitte en hoë motiveringsvlakke wat betrokke is in die proses om ’n sielkundige te word – hierdie twee aspekte skep ’n sterk sin van betekenis en dra by tot persoonlike groei. Verder is selfrefleksie nie net as sneller vir selfinsig geïdentifiseer nie, maar ook as ’n kragtige element wat tot persoonlike groei en outonomie in die studente se reis kan bydra. Die bevindings het verder aangedui dat persoonlike groei ’n positiewe uitkoms van al die deelnemers se ervarings was. Intrapersoonlike dinamika het ook die deelnemers tot groter selfaanvaarding bygestaan. Die studie het getoon dat die studente interpersoonlike groei as ’n positiewe uitkoms van die ervaring geïdentifiseer het en dat positiewe verhoudings met ander as ’n nuttige hanteringsvaardigheid regdeur die jaar gebruik is en dus tot die psigologiese welstandsdomein van omgewingsbemeestering bygedra het. Supervisiepraktyke het ’n positiewe invloed op die psigologiese welstandsdomein van outonomie gehad en het ook tot die studente se persoonlike groei bygedra. Verder het spirituele verdieping gespruit uit die meestersgraadstudente se ervaring van hulle opleiding in professionele sielkunde, en spiritualiteit is as effektiewe hanteringsmeganisme ingespan. Die groepdinamika van die meestersgraadklas en die verhoudings met klaskollegas het as belangrike faktore geblyk wat positief tot die deelnemers se psigologiese welstand bygedra het, spesifiek in die domein van outonomie en positiewe interpersoonlike verhoudings. Laastens het die bevindinge aangedui dat die deelnemers individuele praktiese hanteringstrategieë geïdentifiseer en toegepas het, wat tot die domein van omgewingsbemeestering bygedra het. Oor die algemeen was die belangrikste bevinding dat, alhoewel die ervaring van die proses om ’n sielkundige te word as ’n lang en moeilike reis bekend staan, dit ook lonend kan wees en die potensiaal het om psigologiese welstand te verhoog. Die studie sluit af met ’n bespreking van die implikasies, beperkings en sterk punte van die studie, asook aanbevelings vir toekomstige navorsing.
Thesis (Ph.D. (Psychology))--University of the Free State, 2011
Keywords: Master's students; Phenomenology; Positive psychology; Psychological well-being; Professional training in psychology; Psychology -- Research -- Methodology; Phenomenological psychology; Interpretative phenomenological analysis